A Linear Diubiquitin-Based Probe for Efficient and Selective Detection of the Deubiquitinating Enzyme OTULIN. Issue 10 (19th October 2017) - Weber, Aurelia; Elliott, Paul R.; Pinto-Fernandez, Adan; Bonham, Sarah; Kessler, Benedikt M.; Komander, David; El Oualid, Farid; Krappmann, Daniel
Summary: The methionine 1 (M1)-specific deubiquitinase (DUB) OTULIN acts as a negative regulator of nuclear factor κB signaling and immune homeostasis. By replacing Gly76 in distal ubiquitin (Ub) by dehydroalanine we designed the diubiquitin (diUb) activity-based probe UbG76Dha -Ub (OTULIN activity-based probe [ABP]) that couples to the catalytic site of OTULIN and thereby captures OTULIN in its active conformation. The OTULIN ABP displays high selectivity for OTULIN and does not label other M1-cleaving DUBs, including CYLD. The only detectable cross-reactivities were the labeling of USP5 (Isopeptidase T) and an ATP-dependent assembly of polyOTULIN ABP chains via Ub-activating E1 enzymes. Both cross-reactivities were abolished by the removal of the C-terminal Gly in the ABP's proximal Ub, yielding the specific OTULIN probe UbG76Dha -UbΔG76 (OTULIN ABPΔG76). Pull-downs demonstrate that substrate-bound OTULIN associates with the linear ubiquitin chain assembly complex (LUBAC). Thus, we present a highly selective ABP for OTULIN that will facilitate studying the cellular function of this essential DUB. Graphical Abstract: Highlights: Chemical synthesis of the OTULIN ABPs UbG76Dha -Ub and UbG76Dha -UbΔG76 OTULIN ABPs display high selectivity for labeling OTULIN Chemical tool to monitor OTULIN activity and interactions in cells Substrate-bound OTULIN associates with cellular LUBAC Abstract : Weber et al. report on the chemical synthesis of highly selective OTULIN activity-based probes (ABPs) useful for studying enzymatic activity and cellular functions of the M1-linkage-specific ubiquitin hydrolase OTULIN.